Language usage in Pakistani classrooms (International Journal of Scientific Research and Management (IJSRM), 2017)
The use of code mixing, code switching and language borrowing is frequent in Pakistani classrooms especially when it comes to English language learning. The present study focuses on the ways in which code-switching/mixing or language borrowing is considered helpful in teaching/learning and investigates the issues related to language choice and use in bilingual classroom discourse. The findings reflect the role of L1 as a strategy and aid in the classrooms to enhance students‟ learnability and teachers‟ effectiveness in comprehension and understanding of the concepts.